KINERJA KEUANGAN BERBASIS PENCIPTAAN NILAI, MAKRO EKONOMI DAN DAMPAKNYA TERHADAP RETURN SAHAM SEKTOR PERTAMBANGAN - Retno Endah Supeni* Robiatul Adawiyah** (Universitas Muhammadiyah Jember, 2015)
The purpose of this study was to analyze the effect of partially and simultaneously influence between financeratios (ROA and ROE) and variable macroeconomic (inflation and exchange rate) to return mining stocks listed on the Indonesian stock exchange for period of 2012 – 2014. This study uses multiple linear regression analysis. From the selection of the sample can be obtained 14 mining companies. the results of multiple linear regression is found that the partial with the alpha (α) 0,05 ROA positive and significant effect on stock returns and inflation and has a significant positive effect on stock returns. While Return on Equity(ROE) and exchange rates and no significant negative impact on stock returns mining sector on the stock exchange in Indonesia 2012 – 2014. While simultaneously independent have a significant impact on the mining sector stock returns in the stock exchanges in Indonesia 2012 – 2014.